2006
DOI: 10.1677/joe.1.06784
|View full text |Cite
|
Sign up to set email alerts
|

Peptide YY (PYY)3–36 modulates thyrotropin secretion in rats

Abstract: Peptide YY (PYY) 3-36 is a gut-derived hormone, with a proposed role in central mediation of postprandial satiety signals, as well as in long-term energy balance. In addition, recently, the ability of the hormone to regulate gonadotropin secretion, acting at pituitary and at hypothalamus has been reported. Here, we examined PYY 3-36 effects on thyrotropin (TSH) secretion, both in vitro and in vivo. PYY 3-36 -incubated rat pituitary glands showed a dose-dependent decrease in TSH release, with 44 and 62% reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These findings imply that PYY may have long‐term benefits to reduce excess adiposity and ameliorate metabolic abnormalities associated with obesity through mechanisms independent of effects on food intake, notably stimulation of thyroid function. In keeping with this, PYY3‐36 injection was shown to increase serum levels of thyrotropin in fasted rats (Oliveira et al ., 2006).…”
Section: The Y2 Receptor (Table 2)mentioning
confidence: 65%
“…These findings imply that PYY may have long‐term benefits to reduce excess adiposity and ameliorate metabolic abnormalities associated with obesity through mechanisms independent of effects on food intake, notably stimulation of thyroid function. In keeping with this, PYY3‐36 injection was shown to increase serum levels of thyrotropin in fasted rats (Oliveira et al ., 2006).…”
Section: The Y2 Receptor (Table 2)mentioning
confidence: 65%
“…These findings suggest that PYY may have a longterm benefit to reduce excess adiposity and ameliorate metabolic abnormalities associated with obesity through mechanisms independent of effects on food intake, notably stimulation of thyroid function. In keeping with this, PYY3-36 injection was recently shown to increase serum levels of thyrotropin (thyroid-stimulating hormone) in fasted rats [72].…”
Section: Peptide Yy Knockout Mice and Peptide Yy Transgenic Micementioning
confidence: 68%
“…There have been only a few reports on the relationship between hypothyroxinemia and serum gut hormones, not only in children and infants, but also in adults. In fasting rats, PYY 3–36 at a dose of 3 or 30 μg/kg bodyweight elicited a significant rise in serum TSH observed 15 min after PYY 3–36 injection . It has also been reported that the fasting GLP‐1 level in pediatric human patients with overt hyperthyroidism was significantly increased .…”
Section: Discussionmentioning
confidence: 89%